Asymptotic Expansion for the Derivative of Finite Elements (Journal of Computational Mathematics, 2021)
It is proved in this paper that there exists an expansion for the derivative of the linear finite element approximation to a model Dirichlet problem in a polygonal domain with a piecewise uniform triangulation.